Improvement in CO2 adsorption capacity of cocoa shell through functionalization with amino groups and immobilization of cobalt nanoparticles. Issue 1 (February 2018) - Bargougui, R.; Bouazizi, N.; Brun, N.; Fotsing, P. Nkuigue; Thoumire, O.; Ladam, G.; Woumfo, E. Djoufac; Mofaddel, N.; Derf, F. Le; Vieillard, J.
Graphical abstract: Highlights: Functional cocoa shells were prepared and characterized. Cobalt nanoparticles were immobilized onto APTES-grafted cocoa shells. Maximum CO2 adsorption capacity of 0.24 mmol g −1 . Abstract: The aim of this research is to investigate how (3-aminopropyl)triethoxysilane (APTES) grafting and cobalt nanoparticles (Co-NPs) immobilization may improve the activity of cocoa shell (CS) towards the adsorption of CO2 under ambient temperature. Pure CS are agricultural by-products which are inexpensive and abundantly available. CS powder was functionalized at 80 °C by APTES grafting and modified through the subsequent immobilization of Co-NPs. Physical and thermal properties and stability of the adsorbents have been investigated. Thus, their composition, surface charge, and morphology were determined by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), differential scanning calorimetry (DSC), and zeta potential measurements. CO2 adsorption capacity was remarkably increased from 0.015 mmol g −1 for the raw material to 0.24 mmol g −1 after surface modification, highlighting a promising synergistic effect. The adsorption behavior of CO2 was investigated, which involves both physical and chemical adsorption. We hope that this work will open new prospects to develop high-performance biomass-derived adsorbents.